Introduction - Merve Bedir (A+BE: Architecture and the Built Environment)
There is an increasing need for ensuring high energy savings throughout the building lifecycle, from the early design phases until post occupancy. Utility (services) and firmness (robustness) are principles of good design since Vitruvius, but sustainability was added as a new principle after 1980s, for a distinct understanding, evaluation and action development on energy consumption and environmental impact of buildings. Today, we are able to measure the consumption levels and environmental impact of our buildings, manage their indoor comfort, and combine this further with our personal desires.